A comparative study of gut microbiomes in captive nocturnal strepsirrhines. Issue 10 (13th May 2019) - Bornbusch, Sally L.; Greene, Lydia K.; McKenney, Erin A.; Volkoff, Savannah J.; Midani, Firas S.; Joseph, Gail; Gerhard, William A.; Iloghalu, Uchenna; Granek, Joshua; Gunsch, Claudia K.
Abstract: Feeding strategy and diet are increasingly recognized for their roles in governing primate gut microbiome (GMB) composition. Whereas feeding strategy reflects evolutionary adaptations to a host's environment, diet is a more proximate measure of food intake. Host phylogeny, which is intertwined with feeding strategy, is an additional, and often confounding factor that shapes GMBs across host lineages. Nocturnal strepsirrhines are an intriguing and underutilized group in which to examine the links between these three factors and GMB composition. Here, we compare GMB composition in four species of captive, nocturnal strepsirrhines with varying feeding strategies and phylogenetic relationships, but nearly identical diets. We use 16S rRNA sequences to determine gut bacterial composition. Despite similar husbandry conditions, including diet, we find that GMB composition varies significantly across host species and is linked to host feeding strategy and phylogeny. The GMBs of the omnivorous and the frugivorous species were significantly more diverse than were those of the insectivorous and exudativorous species. Across all hosts, GMBs were enriched for bacterial taxa associated with the macronutrient resources linked to the host's respective feeding strategy. Ultimately, the reported variation in microbiome composition suggests that the impacts of captivity and concurrent diet do not overshadow patterns of feeding strategy and phylogeny. As our understanding of primate GMBs progresses, populations of captive primates can provide insight into the evolution of host‐microbe relationships, as well as inform future captive management protocols that enhance primate health and conservation. Abstract : Variation in gut microbiome composition across four nocturnal primate species.